0066 Chemogenetic Silencing Of CRF Neurons In Paraventricular Nucleus Partially Restores Homeostatic Responses To Chronic Sleep Restriction. (27th April 2018) - Kumar, S; Hsieh, K; McGinty, D; Szymusiak, R
Abstract: Introduction: Homeostatic responses to sleep loss occur following 1–2 days of sleep restriction, but are attenuated following chronic sleep restriction (CSR). CSR can be viewed as a chronic stress, and we hypothesized that activation of corticotropin releasing factor (CRF) neurons in the hypothalamic paraventricular nucleus (PVN) disrupts sleep homeostasis during CSR. We examined the effects of chemogenetic silencing of CRF neurons in the PVN on sleep and EEG measures during CSR in mice. Methods: 7 male CRF-ires-Cre mice received bilateral injections of pAAV-hSyn-DIO-M4D(Gi)-Cherry inhibitory (i)DREADD) and 5 CRF-ires-Cre mice received bilateral injections of pAAV-hSyn-DIO-mCherry (control) targeting the PVN. Mice were implanted with EEG/EMG electrodes. CSR was achieved by intermittent locomotion on a treadmill (2cm/sec), with a 3/12 sec on/off sequence. This sequence was repeated for 3 hrs, followed by 1hr sleep opportunity. Three weeks after AAV injections, 24 hr baseline electrophysiological data were recorded. The 3:1 hr /CSR schedule was applied continuously for five days. Intraperitoneal injections of vehicle (days 3 and 5) or CNO (10 mg/kg; day 4), were administered at zeitgeiber time (ZT) 07. EEG slow-wave activity (SWA) in NREM sleep (% change from baseline values) and sleep wake measures were quantified during 1 hr sleep opportunity at ZT9-10. Results: SWA in mice expressing (i)DREADD on CSR day 3 and 5 (vehicle injection) were not different (115.4 ± 4.7% and 116.2 ± 4.4% of baseline). On day 4 after CNO injection SWA was 135.3 ± 7.9% of baseline. SWA in control mice on CSR day 3, 4, and 5 were similar (117.5 ± 7.8%, 108.9 ± 6.0%, and 114 ± 6.6% of baseline). Total sleep time (TST) in minutes in (i)DREADD expressing mice on CSR day 1, 3, 4 and 5 were 44.1 ± 2.0, 38.2 ± 2.0, 42.1 ± 1.7, and 38.0 ± 1.6. These values for control mice were 42.9 ± 4.1, 39.4 ± 2.8, 36.6 ± 3.6, and 38.2 ± 3.9. Conclusion: These findings support the hypothesis that activation of CRF neurons in the hypothalamic PVN contributes to the suppression of sleep homeostasis during CSR. Support (If Any): VA Merit Award BX00155605 and BX003520.